Economic Thought in the Soviet Union: III.–Economic Heresies at Home and Abroad - Zauberman, A. (Review of Economic Studies, 1949)
Journal Article Economic Thought in the Soviet Union: III.—Economic Heresies at Home and Abroad Get access A. Zauberman A. Zauberman London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 3, 1949, Pages 189–200, https://doi.org/10.2307/2295919 Published: 01 January 1949